Epidemiological evidence for early-onset of enzootic bovine leukosis by L233-Tax-carrying bovine leukemia virus in Japanese Black cattle - TOMIYASU, Takafumi; MORI, Hiroshi; OKAZAKI, Katsunori (Journal of Veterinary Medical Science, 2022)
Bovine leukemia virus (BLV) is the causative agent of enzootic bovine leukosis (EBL), of which annual number has rapidly increased in Japan, and it can be divided into two categories based on the amino acid at position 233 in the Tax protein. Here, we conducted a nationwide surveillance of Japanese Black cattle between 2008 and 2021 in Japan. Among 237 tumor samples, 131 (55.3%) and 101 (42.6%) were harbored L233- and P233-Tax, respectively. Onset of EBL under the age of 3 years by L233-Tax-carrying BLV was frequently observed, especially in the animals born via embryo transfer. We also found that L233-Tax-carrying BLV was more prevalent in dairy areas than non-dairy areas. These findings give insight into prevention of EBL.